2020
DOI: 10.1007/s40291-020-00481-8
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Plasminogen Activator Receptor: A Biomarker for Predicting Complications and Critical Care Admission of COVID-19 Patients

Abstract: The novel coronavirus infection has spread worldwide, causing a wide spectrum of clinical manifestations. Most patients develop moderate clinical illness, but a substantial number will experience severe pneumonia, which may rapidly progress to acute respiratory distress syndrome and multiple organ failure. In this population, soluble urokinase plasminogen activator receptor (suPAR) could serve as a quick triage test and independent marker of clinical severity, hospital and intensive care unit admission, compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…In daily clinical practice, suPAR is an easily measured inflammatory biomarker. Results can quickly be obtained on-site in many hospital settings, even in the emergency department, avoiding the need for samples to be passed through the clinical laboratory, or can even be obtained prior to hospitalization (time to result 20 min) guiding clinicians' decisions [10].…”
Section: Discussionmentioning
confidence: 99%
“…In daily clinical practice, suPAR is an easily measured inflammatory biomarker. Results can quickly be obtained on-site in many hospital settings, even in the emergency department, avoiding the need for samples to be passed through the clinical laboratory, or can even be obtained prior to hospitalization (time to result 20 min) guiding clinicians' decisions [10].…”
Section: Discussionmentioning
confidence: 99%
“…A promising prognostic biomarker called soluble urokinase plasminogen activator receptor (suPAR) is currently used across various hospitals in Europe to manage COVID-19 patients. suPAR is a protein in the blood that reflects immune activation [ 52 ]. It has been demonstrated that the admission suPAR level is an early indicator for the risk of developing severe respiratory failure and requiring mechanical ventilation [ 53 ].…”
Section: Lab Tests Associated With Worse Prognosismentioning
confidence: 99%
“…Using admission suPAR levels for COVID-19 patients, physicians may identify low-risk patients for early discharge to reduce the pressure on COVID-19 emergency departments. Furthermore, physicians may identify high-risk patients for early treatment [ 52 ]. A recent study by Rovina et al evaluated whether the suPAR level at the time of admission could identify patients who would likely develop severe respiratory failure within the first 14 days [ 53 ].…”
Section: Lab Tests Associated With Worse Prognosismentioning
confidence: 99%
“…Azam et al [66] have found median suPAR value of 5.61 ng/ml and suPAR can be used to predict acute kidney injury in SARS-CoV-2 infection. Chalkias et al [67] have found elevated level of suPAR and concluded that suPAR can be utilized as triage biomarker for predicting admission in critical care and complication of SARS-CoV-2 infection. suPAR can be measured on automated platform by enzyme immunoassay, turbidimetric assay, and lateral flow immunoassay quick test which use two types of monoclonal antibodies [64].…”
Section: Utility Of Strem-1 In Sars-cov-2 Infectionmentioning
confidence: 99%